GAMBARAN HEMOGLOBIN DAN ZAT BESI PADA REMAJA PUTRI DI KOTA MANADO - Panjaitan, Nadia Helena; Wowor, Mayer Ferdinand; Berhimpon, Siemona Lydia Eunike (Universitas Sam Ratulangi, 2025)
Background: Anemia is a global public health problem affecting both developing and developed countries with major consequences for human health especially adolescent girls who experience rapid growth and blood loss during menstruation. The incidence of anemia in Indonesia and the world currently needs special attention. Examination of hemoglobin and iron is needed as an initial step in early detection and prevention of increased incidence of anemia. Objective: To determine the picture of hemoglobin and iron in adolescent girls living in Malalayang 1 Barat Village. Methods: Descriptive design with a cross-sectional approach on 30 adolescent girls aged 13-17 years taken by purposive sampling. Data were obtained through laboratory examination of hemoglobin and serum iron levels, measurement of body weight and height, and administration of research forms. Results: There were 28 respondents (93.33%) who had normal hemoglobin levels and 2 respondents (6.67%) who had low hemoglobin levels. There were 24 respondents (80%) who had normal serum iron levels and 6 respondents (20%) who had low serum iron levels. Conclusion: The majority of respondents had normal hemoglobin and serum iron levels (80%), but there were a small number of respondents who experienced iron deficiency (13.33%) and experienced iron deficiency anemia (6.67%).